Crosstalk between HSPA5 arginylation and sequential ubiquitination leads to AKT degradation through autophagy flux. Issue 4 (3rd April 2021) - Kim, Hyo Jeong; Kim, Sun-Yong; Kim, Dae-Ho; Park, Joon Seong; Jeong, Seong Hyun; Choi, Young Won; Kim, Chul-Ho
ABSTRACT: AKT/PKB is downregulated by the ubiquitin-proteasome system (UPS), which plays a key role in cell survival and tumor progression in various types of cancer. The objective of this study was to determine the relationship between the sequential ubiquitination of lysine residues K284 to K214 in AKT and R-HSPA5 (the arginylated form of HSPA5), which contribute to the autophagic/lysosomal degradation of AKT when impaired proteasomal activity induces cellular stress. Results show that proteasome inhibitors (PIs) increased ATE1 (arginyltransferase 1)-mediated R-HSPA5 levels in a reactive oxygen species (ROS)-dependent manner. Further, binding of fully ubiquitinated AKT with R-HSPA5 induced AKT degradation via the autophagy-lysosome pathway. Specifically, the K48 (Lys48)-linked ubiquitinated form of AKT was selectively degraded in the lysosome with R-HSPA5. The deubiquitinase, USP7 (ubiquitin specific peptidase 7), prevented AKT degradation by inhibiting AKT ubiquitination via interaction with AKT. MUL1 (mitochondrial ubiquitin ligase activator of NFKB 1) also played a vital role in the lysosomal degradation of AKT by sequentially ubiquitinating AKT residues K284 to K214 for R-HSPA5-mediated autophagy. Consistent with this finding, despite HSPA5 arginylation, AKT was not degraded in mul1 KO cells. These results suggest that MUL1-mediated sequential ubiquitination of K284 to K214 may serve as a novel mechanism by which AKT is designated for lysosomal degradation. Moreover, binding of R-HSPA5 with fully ubiquitinated AKT is required for the autophagic/lysosomal degradation of AKT. Thus, modulating the MUL1-mediated non-proteasomal proteolysis mechanisms, such as sequential ubiquitination, may prove to be a novel therapeutic approach for cancer treatment. Abbreviations : AKT1: thymoma viral proto-oncogene 1; ATE1: arginyltransferase 1; ATG5: autophagy related 5; CASP3: caspase 3; EGFP: enhanced green fluorescent protein; GAPDH: glyceraldehyde-3-phosphate dehydrogenase; GSK3B; glycogen synthase kinase 3 beta; HA: hemagglutinin; HSPA5/GRP78/BIP: heat shock protein 5; LAMP1: lysosomal-associated membrane protein 1; MAP1LC3B: microtubule-associated protein 1 light chain 3 beta; MEF: mouse embryonic fibroblast; MUL1: mitochondrial ubiquitin ligase activator of NFKB1; NAC: N-acetylcysteine; NEK2: NIMA (never in mitosis gene a)-related expressed kinase 2; NH4 Cl: ammonium chloride; PARP1: poly(ADP-ribose) polymerase family, member 1; PI: proteasome inhibitor; R-HSPA5: arginylated HSPA5; ROS: reactive oxygen species; SQSTM1: sequestome 1; Ub: ubiquitin; USP7: ubiquitin specific peptidase 7.